Hip and fragility fracture prediction by 4-item clinical risk score and mobile heel BMD: a women cohort study - Thulesius Hans; Petersson Christer; Mellström Dan; Albertsson Daniel; Eggertsen Robert (BMC Musculoskeletal Disorders, 2010)
Abstract Background One in four Swedish women suffers a hip fracture yielding high morbidity and mortality. We wanted to revalidate a 4-item clinical risk score and evaluate a portable heel bone mineral density (BMD) technique regarding hip and fragility fracture risk among elderly women. Methods In a population-based prospective cohort study we used clinical risk factors from a baseline questionnaire and heel BMD to predict a two-year hip and fragility fracture outcome for women, in a fracture preventive program. Calcaneal heel BMD was measured by portable dual X-ray laser absorptiometry (DXL) and compared to hip BMD, measured with stationary dual X-ray absorptiometry (DXA) technique. Results Seven women suffered hip fracture and 14 women fragility fracture/s (at hip, radius, humerus and pelvis) among 285 women; 60% having heel BMD ≤ -2.5 SD. The 4-item FRAMO (Fracture and Mortality) Index combined the clinical risk factors age ≥80 years, weight <60 kg, prior fragility fracture, and impaired rise-up ability. Women having 2-4 risk factors showed odds ratio (OR) for hip fracture of 5.9 and fragility fracture of 4.4. High risk group hip fracture risk was 2.8% annually compared to 0.5% for the low risk majority (69%). Heel BMD showed hip fracture OR of 3.1 and fragility fracture OR of 2.6 per SD decrease. For 30 DXA assessed participants mean hip BMD at -2.5 SD level corresponded to a lower BMD at the heel. Five of seven hip fractures occurred within a small risk group of 32 women, identified by high FRAMO Index + prior fragility fracture + heel T-score ≤-3.5 SD. Conclusions In a follow-up study we identified high risk groups for hip and fragility fracture with our plain 4-item risk model. Increased fracture risk was also related to decreasing heel BMD in calcaneal bone, measured with a mobile DXL technique. A combination of high FRAMO Index, prior fragility fracture, and very low BMD restricted the high risk group to 11%, among whom most hip fractures occurred (71%). These practical screening methods could eventually reduce hip fracture incidence by concentrating preventive resources to high fracture risk women.